Дослідження напружено-деформованого стану іонноазотованих зразків із покриттям в умовах ізотермічної та термоциклічної повзучості методом кінцево-елементного аналізу - Рутковський, А. В.; Маркович, С. І.; Михайлюта, С. С.; Rutkovskіy, A.; Markovych, S.; Myhajlyta, S. (ЦНТУ, 2022)
В роботі на основі методу кінцево-елементного аналізу здійснено дослідження напружено-деформованого стану зразка з алюмінієвого сплаву з теплозахисними дифузійними іонноазотованими шарами в умовах ізотермічного та термоциклічного навантаження. Проведено оцінку напружено-деформованого стану алюмінієвого зразка, як без зміцнення, так із теплозахисним дифузійним іонноазотованим поверхневим шаром від одночасного впливу навантаження та температури, а саме в умовах термоциклічної повзучості. Порівняна оцінка напружено-деформованого стану 1/8 зразка з алюмінієвого сплаву АЛ21 та із зміцненим поверхневим шаром здійснювалася з використанням програмного пакета NАSТRАN. Встановлено, що значна частина еквівалентних напружень сприймається зміцненим поверхневим шаром при збереженні несучої здатності основи. Цим підтверджується підвищення опору композиції “основа-покриття” як ізотермічній так і термоциклічній повзучості. Крім того, за допомогою методу кінцево-елементного аналізу можна передбачити роботу деталей циліндропоршньової групи, а саме час і місце виникнення тріщини при зміні навантаження та температури. One of the advanced methods of increasing the thermal stability of the pistons of internal combustion engines is ionic nitriding (ion-plasma nitriding). At the same time, the study of the stress - strain state of a sample of aluminum alloy with heat - protective diffusion ion - nitrided layers under conditions of thermocyclic loading (simultaneous action of load and temperature) is an urgent task. The application of the finite element analysis method makes it possible to predict the operation of the parts of the cylinder-piston group, namely the time and place of the crack when the load and temperature change. When calculating the stress-strain state, the peculiarities of their geometric parameters, properties of structural material, type of calculation (static, thermal, etc.), and conditions of force and temperature load acting on them were taken into account. The calculation was performed using real experimental samples. The method of calculating the stress-strain state of the composition "base - coating" taking into account operational and technological factors consists of several stages: solving the problem of non-stationary thermal conductivity to determine the residual stresses resulting from coating; determination of stresses from power and temperature load; obtaining the stress-strain state by the method of superposition. Using the finite element analysis method, the stress-strain state of the aluminum sample was evaluated, both without hardening and with a heat-protective diffusion ion-nitrided surface layer from simultaneous exposure to load and temperature, namely under conditions of thermocyclic creep. To more accurately determine the equivalent stresses, the calculations were performed on 1/8 of the sample. Comparative evaluation of the stress-strain state of 1/8 of the sample of aluminum alloy AL21 and with a reinforced surface layer was performed using the software package NASTR. Thus, based on the analysis of the stress - strain state of the aluminum alloy sample with heat-protective diffusion ion - nitrided layers under thermocyclic loading (simultaneous action of load and temperature) it is established that a significant part of equivalent stresses is perceived by the strengthened surface layer. This confirms the increase in the resistance of the composition "base-coating" of both isothermal and thermocyclic creep. In addition, with the help of the finite element analysis method, it is possible to predict the operation of the parts of the cylinder-piston group, namely the time and place of the crack when the load and temperature change.
Investigation of the Stress-strain State of Ion-nitrogen-coated Specimens Under Conditions of Isothermal and Thermocyclic Creep by Finite Element Analysis
Keywords: напружено-деформований стан; метод кінцево-елементного аналізу; основа; покриття; ізотермічна та термоциклічна повзучість; stress-strain state; method of finite-element analysis; base; coating; isothermal and thermocyclic creep